Tillich’s Theodicies - Shearn, Samuel (Modern theology, 2023)
This essay explores the development of Tillich’s writings on the relationship between divine providence and suffering, and his approach to theodicy. First, I attend to the various stations of his early life and his earliest writings in various genres. Here we see the instrumental-pedagogical theodicies of his student days and earliest preaching give way to an increased emphasis on the suffering of God. However, unlike many twentieth century theologies of suffering, Tillich retains a strong teleological notion of divine providence, even in the face of the horrors of the First World War. Second, I analyse Tillich’s American systematics and sermons against the background of his early writings, characterising his writings as a Hegelian approach to suffering, subsuming the individual under the teleology of divine creativity.